Novel gene manipulation approaches to unlock the existing bottlenecks of CAR-NK cell therapy - Fatemeh Dehghan; Yekta Metanat; Mandana Askarizadeh; Ehsan Ahmadi; Vahid Moradi (Frontiers in Cell and Developmental Biology)
Currently, CAR-T cell therapy is known as an efficacious treatment for patients with relapsed/refractory hematologic malignancies. Nonetheless, this method faces several bottlenecks, including low efficacy for solid tumors, lethal adverse effects, high cost of autologous products, and the risk of GvHD in allogeneic settings. As a potential alternative, CAR-NK cell therapy can overcome most of the limitations of CAR-T cell therapy and provide an off-the-shelf, safer, and more affordable product. Although published results from preclinical and clinical studies with CAR-NK cells are promising, several bottlenecks must be unlocked to maximize the effectiveness of CAR-NK cell therapy. These bottlenecks include low in vivo persistence, low trafficking into tumor sites, modest efficacy in solid tumors, and sensitivity to immunosuppressive tumor microenvironment. In recent years, advances in gene manipulation tools and strategies have laid the groundwork to overcome the current bottlenecks of CAR-NK cell therapy. This review will introduce the existing gene manipulation tools and discuss their advantages and disadvantages. We will also explore how these tools can enhance CAR-NK cell therapy’s safety and efficacy.